P4.115 High uptake of effective expedited partner therapy among young women with sti and their partners in south africa. (8th July 2017) - Garrett, Nigel; Maharaj, Bhavna; Osman, Farzana; Ngubane, Nontobeko; Shozi, Hlengiwe; Ngomane, Noluthando; Ngobese, Hope; Gibbs, Andrew; Kharsany, Ayesha; Rompalo, Anne; Mindel, Adrian
Abstract : Introduction: Expedited Partner Therapy (EPT) for STIs delivered by the index case or through pharmacies has been implemented in some settings in the US. In South Africa, partner notification through the provision of a contact card to the patient reminding the partner to seek treatment has been unsuccessful (partner treatment rates of 17%). Here, we explored the feasibility and acceptability of index case delivered EPT among young women in a high HIV incidence setting. Methods: HIV negative women, aged 18–40 years were screened for chlamydia, gonorrhoea (Xpert CT/NG) and trichomonas (OSOM) at an urban primary health care clinic. Women with STIs were treated with stat doses of antibiotics and were offered EPT packs, which included medication, condoms and an information leaflet for the current partner(s). An EPT questionnaire was administered telephonically one week later, and women were reviewed in clinic after 6 and 12 weeks. Results: A total of 267 women, median age 23 (IQR 21–27), were screened and 63 (23.6%) were diagnosed with a STI. Of these, 62/63 (98.4%) were offered and 54/62 (87.1%) accepted EPT for their regular partner. Two women chose EPT for one additional casual partner. At telephonic follow-up 47/54 (87.0%) stated that they had successfully delivered EPT, i.e. the partner ingested the medication either observed 41/54 (75.9%) or unobserved 6/54 (11.1%). Only five women (9.2%) still had to deliver EPT and one partner refused. Some women reported that they (17.5%) or their partners (4.8%) experienced minor drug side effects consistent with antibiotic profiles, but no allergic reactions or social harms were reported. Of the first 53 women completing follow up reinfection rates were lower amongst women receiving EPT (1/47, 2.1%) compared to those not receiving EPT (2/6, 33.3%), p=0.031. Conclusion: EPT uptake among young South African women and their partners was high and could play an important role in reducing reinfection rates and HIV risk. Larger studies should evaluate the feasibility of implementing this strategy at population level. Support: : This work was co-funded by the South African Medical Research Council and the NIH (AI116759)